2010
DOI: 10.1017/s174217051000044x
|View full text |Cite
|
Sign up to set email alerts
|

Incorporating native plants into multifunctional prairie pastures for organic cow–calf operations

Abstract: The multifunctional agronomic, ecological, economic and social uses of grass-based agricultural systems in peri-urban Marion County, Iowa, were the subject of investigation from 2003 to 2005. Following a sociocultural analysis that identified diverse motivations of cow–calf operators, an on-farm, agroecological experiment was established with a member of the study group. The objective of the experiment was to investigate the feasibility of establishing a multifunctional prairie pasture in response to the opera… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
9
0

Year Published

2010
2010
2015
2015

Publication Types

Select...
4
1

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(9 citation statements)
references
References 54 publications
0
9
0
Order By: Relevance
“…Under organic standards, organic ruminant livestock producers are required to rely on forage-based livestock feed including, in season, management of grazed rangeland or pastures. Some studies suggest that improved grazing management, including the use of legumes, can be not only a cost-effective option but can also promote substantial SOC gains on the extensive acreage of often degraded, permanent grasslands in North America [16,68,69].…”
Section: Soil Organic Matter Storagementioning
confidence: 99%
See 2 more Smart Citations
“…Under organic standards, organic ruminant livestock producers are required to rely on forage-based livestock feed including, in season, management of grazed rangeland or pastures. Some studies suggest that improved grazing management, including the use of legumes, can be not only a cost-effective option but can also promote substantial SOC gains on the extensive acreage of often degraded, permanent grasslands in North America [16,68,69].…”
Section: Soil Organic Matter Storagementioning
confidence: 99%
“…The oversupply of N and P is considered a major driver of biodiversity loss in temperate grasslands [2]. The avoidance of this causal factor and reduced likelihood of overgrazing in organic management may promote the establishment of more diverse and multifunctional swards, as reported from Iowa [16]. There is a need also for more farmland biodiversity studies under semi-arid conditions common to much of North America, as results from more temperate regions such as Northern Europe may not transfer to these different climatic and ecological conditions.…”
Section: Vegetative Diversitymentioning
confidence: 99%
See 1 more Smart Citation
“…This difference suggests that part-time operators may be more willing candidates for long-term perennial vegetation projects and habitat development, such as the multifunctional prairie pasture system developed with a member of this group in a follow-up agroecological on-farm experiment 71 . Pasture systems among full-time integrated cattle and grain crop operators were generally 'integrated fields' used for both row crop and cattle, and were dependent on the season and the crop rotation.…”
Section: Typology Class Comparisonmentioning
confidence: 99%
“…In the second phase of this project, a full-time cow-calf operator from the study group, operating in a direct-market scheme, demonstrated the potential for prairie pastures to enhance the biodiversity and sustainability of his grassland system 71 . Government programs, such as the CSP and EQIP, can provide incentives for sustaining a farm landscape consisting of diverse, grass-based agricultural systems that support rural livelihoods and environmental quality.…”
Section: Conclusion From the Socio-cultural Studymentioning
confidence: 99%